Pelatihan Robotika Sebagai Upaya Meningkatkan Kompetensi Keahlian Siswa SMK Daarut Tauhiid Bandung - Muhammad Taufik Dwi Putra; Deden Pradeka; Anugrah Adiwilaga; Munawir Munawir; Dhimaz Purnama Adjhi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The rapid scientific development of robotics technology must be in line with efforts to increase the creativity and skills of human resources. Responding to these challenges, it is necessary to implement a robotics technology-based learning curriculum as early as possible starting from the school. However, there are some problems such as curriculum with robotics technology which is still rarely found in Indonesian schools. The purpose of this service is to improve the skills of students of SMK Daarut Tauhid through Robotics training. This method of devotion uses the method of lectures, hands-on practice, and interactive discussions. The number of participants in this training was 20 (twenty) students with activity evaluation instruments using g-form surveys and was analyzed descriptively. The results of this service show that student participants tend to better understand the scientific concepts of robotics technology when faced with real hardware compared to simulations using software. With this training, it’s hoped that knowledge and skills in robotics technology and science among students will increase.